2017
DOI: 10.1080/00071668.2017.1304530
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the economic potential of reducing broiler lameness

Abstract: 1. The present study was designed first to explore the potential economic benefits of adopting management practices to reduce lameness in broiler farms, and second to explore farmers' possible perceptions of this potential in the Swedish context. The likely financial effects were addressed using a normative economic model, whereas a questionnaire-based survey was used to obtain in-depth knowledge about the perceptions of a group of broiler farmers in Sweden. 2. The three alternative practices (out of 6 tested)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 42 publications
4
18
0
Order By: Relevance
“…In many cases, birds are culled due to performance issues that may or may not be related to poor welfare. Around half of the birds culled on the grounds of animal welfare can be attributed to lameness (Gocsik et al 2017), and this was confirmed elsewhere (Applied Group 2018; personal communication). The death of an individual bird is not necessarily a welfare problem; indeed, death may be seen as the ultimate welfare solution (Dawkins 1990).…”
Section: Animal Welfare Indicatorssupporting
confidence: 55%
“…In many cases, birds are culled due to performance issues that may or may not be related to poor welfare. Around half of the birds culled on the grounds of animal welfare can be attributed to lameness (Gocsik et al 2017), and this was confirmed elsewhere (Applied Group 2018; personal communication). The death of an individual bird is not necessarily a welfare problem; indeed, death may be seen as the ultimate welfare solution (Dawkins 1990).…”
Section: Animal Welfare Indicatorssupporting
confidence: 55%
“…Economic losses are largely associated with lameness and its consequences, such as decrease in production parameters, increase in mortality, culling, and condemnation of carcasses at slaughterhouses. Staphylococcosis also contributes to reduced poultry welfare due to pain, stress, and decreased locomotive abilities [ 3 , 6 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is because the increase in investment will enrich the environment and then improve welfare. Welfare improvements can also reduce health costs [40][41][42][43]. Based on previous studies, the authors propose making full use of available technology to improve the environment, such as lighting and cage furnishing [20], and eventually improve animal welfare.…”
Section: Discussionmentioning
confidence: 99%